2012
DOI: 10.1002/mabi.201200085
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Interactions of a Water‐Soluble Supramolecular Polymer Complex of Carbon Nanotubes with Human Epithelial Colorectal Adenocarcinoma Cells

Abstract: Water-soluble, PAX-loaded carbon nanotubes are fabricated by employing a synthetic polyampholyte, PDM. To investigate the suitability of the polyampholyte and the nanotubes as drug carriers, different cellular interactions such as the human epithelial Caco-2 cells viability, their effect on the cell growth, and the change in the transepithelial electrical resistance in Caco-2 cells are studied. The resulting complex is found to exhibit an effective anti-cancer effect against colon cancer cells and an increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…For the delivery of paclitaxel in Caco-2 cells single-walled carbon nanotubes conjugated with a synthetic polyampholyte were used. Paclitaxel-SWCNTtreated Caco-2 and HT-29 cells showed greater anticancer effects when compared with alone paclitaxel (Lee and Geckeler, 2012;Wu et al, 2015). The same types of results have been found in Eudragit ® -irinotecan loaded CNTs (Zhou et al, 2014).…”
Section: Carbon Nanotubessupporting
confidence: 71%
“…For the delivery of paclitaxel in Caco-2 cells single-walled carbon nanotubes conjugated with a synthetic polyampholyte were used. Paclitaxel-SWCNTtreated Caco-2 and HT-29 cells showed greater anticancer effects when compared with alone paclitaxel (Lee and Geckeler, 2012;Wu et al, 2015). The same types of results have been found in Eudragit ® -irinotecan loaded CNTs (Zhou et al, 2014).…”
Section: Carbon Nanotubessupporting
confidence: 71%
“…Several antitumour-drug-carriers-strategies based on CNTs have been developed. In one of them, the single-walled carbon nanotubes (SWCNTs) conjugated with a synthetic polyampholyte for the delivery of paclitaxel demonstrated greater anticancer effects in Caco-2 and HT-29 cells compared to paclitaxel alone [3,155]. A similar effect was observed using Eudragit ® -irinotecan-loaded CNTs [3,156].…”
Section: Carbon-based Nanomaterialsmentioning
confidence: 87%
“…52 Among antimicrotubules, paclitaxel (PTX) and docetaxel (DTX) have been widely studied. [53][54][55][56][57][58][59][60][61][62][63] Arya et al 53 reported that SWCNTs increase PTX activity against lung cancer by reactive-oxygen-species-dependent synergy between CNTs and PTX. They confirmed the efficacy on A549 and NCI-H460 cell lines.…”
Section: Cnts As Antimicrotubule Carriersmentioning
confidence: 99%